Agrarian Conflict in Urutsewu: Political Ecology Approach - Adelia Salwa; Ashari Ashari; Henny Muldia; Hesti Wulandari; Mita Harniawati; Putri Meiensi; Rani Rani; Rohyadi Andika Chandra; Seli Indriani; Jagad Aditya Dewantara (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This book discusses the management of natural resources that are prone to conflict, such as the exploitation of mining materials. In this case, usually the parties involved involve several elements such as the community, local government, non-governmental organizations or environmental NGOs, and of course companies that will carry out mining. In this case, of course, to gain profit and the local government supports mining in order to increase regional income. However, in this case it is not in line with the community and environmental NGOs who refuse mining on the grounds that it disrupts the economic well-being of residents from their original livelihoods and ecological damage due to mining activities. This conflict has frequently occurred in Indonesia since 1999 and has spread to various regions, from Sumatra, Java, Kalimantan, Sulawesi, Nusa Tenggara to Papua. Gold mining in Papua by 2 Agrarian Conflicts in Urutsewu: Political Ecology Approach PT Freeport Indonesia, for example, is one of the causes of the prolonged conflict. The trigger for this conflict is not only about the welfare of local people who are being ignored by the government and PT Freeport Indonesia. Even deeper, the conflict is also rooted in environmental damage due to the dredging of Mount Ersberg's gold deposit.